2003
DOI: 10.1161/01.hyp.0000056998.83031.22
|View full text |Cite
|
Sign up to set email alerts
|

α 2A -Adrenergic Receptors Mediate Sympathoinhibitory Responses to Atrial Natriuretic Peptide in the Mouse Anterior Hypothalamic Nucleus

Abstract: Abstract-In the rat, activation of ␣ 2 -adrenergic receptors in the anterior hypothalamic nucleus inhibits sympathetic nervous system activity. Furthermore, local release of atrial natriuretic peptide inhibits norepinephrine release in this nucleus, blocking local activation of ␣ 2 -adrenergic receptors, and thereby contributes to NaCl-sensitive hypertension in spontaneously hypertensive rats. To further test the specificity of this mechanism, either ␣ 2 -adrenergic receptor agonists or atrial natriuretic pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The D 2 upregulation is consistent with the previously mentioned studies in deficient rat pups. 41 Although central a 2A receptors, 47 dopamine b-hydroxylase 48 and D 2 receptors 49 are all involved in blood pressure regulation, given that there was no difference in blood pressure at this time, and the inconsistency between sufficient groups, it seems unlikely that these factors are involved in o-3 fatty acid deficiency-mediated hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…The D 2 upregulation is consistent with the previously mentioned studies in deficient rat pups. 41 Although central a 2A receptors, 47 dopamine b-hydroxylase 48 and D 2 receptors 49 are all involved in blood pressure regulation, given that there was no difference in blood pressure at this time, and the inconsistency between sufficient groups, it seems unlikely that these factors are involved in o-3 fatty acid deficiency-mediated hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…In another study, Peng et al . showed that the α 2a AR has a sympathoinhibitory role in the brain [33]. Furthermore, α 2 AR subtypes have been demonstrated to control the release of catecholamines from sympathetic nerves and from adrenal medulla [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although injection of supraphysiological dosages of CNP may not exclude coactivation of NPR-A, this study suggests involvement of NPR-B in central regulation of autonomic nerve activity. In addition, ANP was able to mediate sympatho-inhibitory responses when injected locally into the anterior hypothalamic nucleus of conscious mice; however, CNP was not applied in this study [107]. When administered intravenously into conscious sheep, CNP, along with ANP and BNP, has been reported to enhance reflex bradycardia as induced by repetitive intravenous injection of a serotonin agonist [108].…”
Section: Effects On the Autonomic Nervous Systemmentioning
confidence: 68%